Solid construction waste management in large civil construction companies through use of specific software - case study - Caio Dalla Zanna (Acta Scientiarum. Technology, 2017)
In the current construction market there is a high demand for sustainability. In addition to that the Brazilian government is enacting tougher and tougher legislation on the disposal of solid construction waste. These demands increasingly make the construction company responsible for the entire lifecycle of its waste as well as the accompanying cost and environmental impact of solid waste. A software program was used in the research which allows construction companies gather information about waste. This helps the decision makers, at all different levels of the company improving waste management through better decisions. The software program was used during the construction of two residential buildings, constructed by a large construction company in the South of Brazil. Five key performance indicators were used by the construction company team: Generated Waste Height (cm), cost per built area (R$ m-²), Waste Segregation Quality Index (WSQI), Effective Waste Management Index (EWMI) and Waste Management Quality Index (WMQI). After four months the total cost of waste management was R$ 83,551.71 for site A and R$ 91,668.02 for site B. About 70% of the waste was raw material waste. The software program provided information not previously available, which made it possible to calculate the cost of material loss, indicating corrective actions, all without losing sight of cost reduction opportunities for the management of Solid construction Waste (SCW).